Explosive activity at Ubinas volcano (Peru) during March 2006 to April 2007 - Rivera Porras, Marco Antonio (2007)
Póster (21a-P-08) presentado en Cities on Volcanoes 5 conference : Shimabara, Japan, November 19-23, 2007.